DIBALIK ALASAN NABI MUHAMMAD DIJADIKAN WASILAH DALAM BERDOA: KAJIAN LINGUSITIK KOGNITIF - Nailah Sa'diyatul Fitriah (Prasasti: Journal of Linguistics, 2020)
According to Cognitive Linguistic theory, humans think in three ways. Two of them are thinking prototypically and ideally. One of the example of these ways can be seen from how Muslems use the blessings of the Prophet Muhammad as a bridge in granting their dua. Most of Moslems assume that the Prophet Muhammad could intercede for prayer. Based on this interesting issue, this article aims to find out the prototypes of PROPHET MUHAMMAD idealized by Moslems in translation of Maulid Simtudduror book.This book contains of a range of praise, history, and prayers offered to the Prophet Muhammad as a wasilah for their  prayers. By using Rosch et al (1991) prototype model analysis method and an ideal cognitive model based on the stereotype model of society initiated by Lakoff (1987), it can be concluded that the prototype of PROPHET MUHAMMAD idealized by Islam and Moslems show some features of the Prophet Muhammad in several MODELS bringing blessings for all human beings in this world. Thus, most of Moslems believe that PROPHET MUHAMMAD can be a wayin helping  them to grant  their prayers.